Analisis Faktor Harga dan Mutu dalam Keputusan Pembelian Konsumen terhadap Sepeda Motor Listrik GESITS di Indonesia - Aji, Achmad Maezar Bayu; Firmansyah, Alfian; Macpal, Stelly Julia (Jurnal EMT KITA, 2024)
In the development of the electric motorbike industry in Indonesia, this research focuses on the influence of price and quality on vehicle purchasing decisions, especially Gesits electric motorbikes. Manufacturers, facing fierce competition, continue to improve product quality, price and design to meet consumer needs. By involving 52 respondents (25% of the population of 207 units sold), this study exceeds the recommended minimum sample size. The results of multiple linear regression analysis show that price and quality factors have a significant correlation and strongly influence Gesits purchasing decisions. This research contributes to understanding the purchasing factors of electric motorbikes, providing strategic insight for manufacturers in improving quality and pricing.